Gambaran Kejadian Diare pada Balita di Rumah Sakit Umum Daerah Wangaya Denpasar - Komang Yasmika Utami; Ni Wayan Armerinayanti; Anak Agung Oka Lely (Aesculapius Medical Journal, 2023)
Abstract [Overview of the Diarrhea Incidence in Toddlers at the Wangaya Regional General Hospital, Denpasar] Diarrhea is a bowel disease with a frequency of 3 or more times per day which is soft, liquid and can be accompanied by blood, mucus, fat, or undigested food particles. Diarrhea is the main cause of death for children under the age of 5 years in Indonesia, due to malnutrition. The severity of diarrheal disease is determined by nutritional status, duration of diarrhea, degree of dehydration, comorbidities and length of stay in hospital. In the province of Bali, the incidence of diarrhea in children under five years includes 1,275 cases and the highest case finding of diarrhea in children under five years is in the city of Denpasar. This study aims to determine the description of diarrheal disease in children under five years at Wangaya General Hospital Denpasar from January 2020 - July 2021. This study is a descriptive study with a cross sectional design. The research subjects were toddlers aged 12-60 months who were selected based on the purposive sampling method. Collecting data using secondary data from the medical records of the Wangaya Regional General Hospital Denpasar, then analyzed using a univariate test through the SPSS computer program. The results showed that all children under five years with diarrhea in Wangaya General Hospital Denpasar experienced acute diarrhea. The majority of toddlers with diarrhea at the Wangaya General Hospital Denpasar experienced mild or moderate dehydration, received less than 5 days of treatment, experienced symptoms of watery bowel movements, vomiting and fever when they entered the hospital and improved when they were brought home. Keywords : diarrhea, duration of diarrhea, degree of dehydration, length of stay in hospital